Medicinal compounds and biotechnology of Amaryllidaceae alkaloids in Lycoris radiata - Chen, Jia-Xu; Zheng, Jiafeng; Cai, You-Ming; Xu, Jun-Xu; Sun, Yi; Yang, Zhen; Yang, Feng; Chen, Mo-Xian; Chen, Yu; Li, Qing-Zhu (Frontiers in Plant Science, 2025)
Lycoris radiata, known for its striking floral patterns and vivid colors, holds significant ornamental value and is widely admired by the public. As research on Lycoris species progresses, scientists have uncovered their significant medicinal potential. These plants are particularly valued for their alkaloid compounds, which exhibit important pharmacological properties, especially strong antibacterial effects. This study systematically investigates the medicinal properties of Lycoris alkaloids. Through a comprehensive review, we analyze the various types of alkaloids present in Lycoris species. It sheds light on their synthetic mechanisms and elucidates their multifaceted functions, providing a detailed understanding of their pharmacological potential. Moreover, this paper highlights recent breakthroughs in alkaloid research, presenting the latest advancements in this field. By systematically documenting and elucidating these aspects, this study aims to provide a comprehensive understanding of the medicinal value of Lycoris and the intricate roles played by its alkaloid constituents.